Makna Lafaz Wālidain Dan Abawain Dalam Al-Qur’an: Analisis Semiotika Roland Barthes - Zahra Baiti Nur Aziah; Hamda Malik (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study examines the Qur’anic terms wālidain and abawain through Roland Barthes’ semiotic approach, encompassing three levels of meaning: denotative, connotative, and myth. Primary data were drawn from the Qur’an, while secondary data came from classical and contemporary tafsir works, Arabic lexicons, and relevant scholarly studies. Using a qualitative text analysis method, each occurrence of wālidain and abawain was classified according to its Qur’anic context. The findings reveal that, at the denotative level, both terms refer to parents, yet they carry distinct linguistic nuances: wālidain emphasizes the biological relationship, whereas abawain conveys the father’s role as the family’s representative figure. At the connotative level, their usage is influenced by socio-cultural context and the moral message of the verse. At the mythic level, wālidain constructs a narrative of unconditional emotional devotion, while abawain conveys a narrative of structural responsibility within the family. These results affirm the relevance of Barthes’ semiotics in Qur’anic exegesis and contribute to a deeper understanding of parent–child relationships from the Qur’anic perspective.